Development of Xanthyletin-Loaded Nanoparticles for the Control of Leucoagaricus gongylophorus - Cristiane de Melo Cazal; Moacir Rossi Forim; Ana Paula Terezan; Andreia Pereira Matos; Gracielle Oliveira Sabbag Cunha; Maria Fátima das Graças Fernandes da Silva; Paulo Cezar Vieira; Fernando Carlos Pagnocca; João Batista Fernandes (Molecules)
This study describes the development, characterization and in vitro evaluation of poly(ε-caprolactone) (PCL) nanoparticles loaded with xanthyletin for the control of Atta sexdens rubropilosa through the inhibition of its symbiotic fungus Leucoagaricus gongylophorus. Nanoparticles were prepared via interfacial polymer deposition, with formulation NC5 selected based on optimal physicochemical properties. NC5 exhibited an encapsulation efficiency of 98.0%, average particle size of 304 nm and zeta potential of −29.3 mV. Scanning electron microscopy confirmed spherical morphology and the absence of crystalline residues. The formulation remained physically stable for four months at 4 °C. In vitro release showed biphasic behavior, with an initial burst followed by sustained release. Under UV exposure, NC5 enhanced xanthyletin photostability by 15.4-fold compared to the free compound. Fungicidal assays revealed 76% inhibition of fungal growth with NC5, compared to 85% with free xanthyletin. These results support the potential application of xanthyletin-loaded PCL nanoparticles as a stable and controlled delivery system for the biological control of leaf-cutting ants by targeting their fungal mutualist. Further in vivo studies are recommended to assess efficacy under field conditions.